2021
DOI: 10.4103/jpcdoh.jpcdoh_9_20
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers in Saliva as Diagnostic Tool in Early Diagnosis of Oral Submucous Fibrosis

Abstract: The potentially malignant lesions of oral cavity pose a sensitive challenge to the public health status. The risk is considerably high of malignant transformation of oral submucous fibrosis (OSMF) into oral cancer. The more rapidly they get diagnosed early, the better it is for public oral health. The need of the hour is to put into general practice the minimally invasive and noninvasive procedures of diagnostics for these lesions. Salivary biomarkers are recently advanced diagnostic tools fit for the requirem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
1
0
0
Order By: Relevance
“…In our research, we discovered that the least amount of people is aware of the impact of acid–base balance on periodontal pockets. [ 22 ] This is in line with the findings of Axelsson and Lindhe, who investigated the impact of regulated oral hygiene techniques on caries and periodontal disease in adults and concluded that dental caries and periodontal disease are the outcomes of poor oral hygiene.…”
Section: Discussionsupporting
confidence: 86%
“…In our research, we discovered that the least amount of people is aware of the impact of acid–base balance on periodontal pockets. [ 22 ] This is in line with the findings of Axelsson and Lindhe, who investigated the impact of regulated oral hygiene techniques on caries and periodontal disease in adults and concluded that dental caries and periodontal disease are the outcomes of poor oral hygiene.…”
Section: Discussionsupporting
confidence: 86%
“…These biomarkers were detected by methylated polymerase chain reaction (PCR), real-time PCR, western blotting, and staining procedures. 5 6 However, the biopsy sometimes is an invasive procedure with low patient acceptance. Liquid biopsy shows the noninvasive detection of components in biofluids, such as blood serum and saliva.…”
Section: Introductionmentioning
confidence: 99%